A reterritorialização dos barqueiros de Babaçulândia (TO) atingidos pela Usina Hidrelétrica de Estreito (MA) - Silva, Súsie Fernandes Santos (2018)
The construction of the Estreito Hydroelectric Power Plant (MA) caused social, environmental and economic impacts to the residents of 2 municipalities of Maranhão and 10 municipalities of Tocantins. Among the impacts, the alteration in the territory, caused by the compulsory migrations that interfered in the social, economic and political relations of the inhabitants of the city of Babaçulândia (TO), altering the traditional way of producing and living. Based on this information, this study reveals indicators related to the observation and description of the panorama of the construction of the Estreito Energy Hydroelectric Plant (UHEE), from 2007 to 2011, located in the Tocantins River, on the border between the states of Maranhão and Tocantins. This research presents the impacts of this enterprise in the territory and in the accomplishment of the self-support activities of the boatmen associated to the Association of Boatmen of Babaçulândia (TO), as well as the presentation of reports on how the deterritorialization happened, the process of negotiation of the indemnifications and the reterritorialization of the studied group, composed of 15 men. Methodologically, the study was developed based on qualitative research. The interview script have open and closed questions about the identification of the research participant, the memory of the work and the place impacted, production and income, the impacts of the enterprise from the expropriation process to the definition of a new location were applied. housing and collective compensatory measures. The interview script was applied in April and May 2017. The methodological tools in oral history, field visits, photographs and participation in assemblies of the Association of Boatmen of Babaçulândia (TO) were used to compose the data. The category reached by dams and boatmen and their relations with the territory and the landscape sustained the research in the theoretical terms. During the survey it was understood that in the destabilization of the boatmen's territory, the indemnities occurred, with values received individually; and as an association - through compensatory measures - with the construction of a headquarters shed with some equipment and furniture for the association and a catamaran boat, also equipped with cooking and leisure utensils. There were some difficulties for those resettled in rural areas, such as lack of drinking water for human and animal consumption. Other difficulties are related to the lack of work due to the fact that there are no beaches on the Maranhão margin or river dwellers to be transported, a situation that makes it impossible to continue working as a boatman and the lack of other types of work in which boatmen can be inserted. In view of the above, it is also observed that, despite the receipt of the compensatory measures for the association, the boatmen are not carrying out works capable of supplying their needs for the production of incomes in favor of their family support. To do so, it is suggested to hold events on the catamaran anchored in the waterfront, such as the sale of food and beverages during certain days of the week at night. And for the use of the shed, it is suggested to realize moments in which the members can commercialize products and services produced by their family groups.